Novel Colloidal Forming of Ceramics - Huang, Yong.; Yang, Jinlong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
"Novel Colloidal Forming of Ceramics(3y (Bdiscusses several new near-net-shape techniques for fabricating highly reliable, high-performance ceramic parts. These techniques combine injection molding and the colloidal forming process. The book not only introduces the basic theoretical development and applications of the colloidal injection molding of ceramics, but also covers tape casting technology, the reliability of the product, and the colloidal injection molding of Si3N4 and SiC, as well as the low-toxicity system. The book is intended for researchers and graduates in materials science and engineering. Mr. Yong Huang and Dr. Jinlong Yang are both professors at the Department of Materials Science and Engineering, Tsinghua University, China.s
Aqueous Colloidal Injection Molding of Ceramics Based on Gelation -- Gel-Tape-Casting of Ceramic Substrates -- Gelation Forming Process for Low Toxicity System -- Generation, Development, Inheritance, and Control of the Defects during the Transformation from Suspension to Green Body -- The Gel-Casting of Non-Oxide Ceramics -- Application of New Colloidal Forming -- The New Methods and Techniques Based on Gel-Casting.
Keywords: Chemistry, Physical organic; Machinery; Materials Science; Ceramics, Glass, Composites, Natural Methods; Physical Chemistry; Manufacturing, Machines, Tools